Pedagogical practices that influence professional identity formation in baccalaureate nursing education: A scoping review. (October 2020) - Simmonds, Anne; Nunn, Alexandra; Gray, Mikaela; Hardie, Catherine; Mayo, Samantha; Peter, Elizabeth; Richards, Jessie
Abstract: Objectives: The purpose of this review was to identify pedagogical practices that contribute to professional identity formation in undergraduate nursing education and to map the components of professional identity described within these practices. Design: A scoping review using a six-stage methodological framework was used to capture a range of evidence describing how professional identity has been conceptualized and integrated into nursing curriculum. Data sources: Databases searched included: Ovid MEDLINE: Epub Ahead of Print, In-Process & Other Non-Indexed Citations, Ovid MEDLINE® Daily and Ovid MEDLINE® 1946-Present, EBSCO CINAHL (1981 to present), OVID PsycINFO (1806 to Present), ProQuest ERIC, ASSIA, and Sociological Abstracts. Additional studies were identified by scanning the reference lists of relevant articles. Review methods: The study team collaboratively designed the data charting table and two coauthors independently screened the studies using Covidence software. Qualitative content analysis was used to categorize learning outcomes into five components of professional identity that were associated with pedagogical practices identified in the studies. Results: A total of 114 peer-reviewed journal articles were initially charted. Articles were categorized as intervention studies (46, 40%), perspective studies (40, 35%), theoretical papers (17, 15%), or reviews (11, 10%). To ensure feasibility in collating and reporting the results, the review focused on the 46 empirical intervention studies that described associations between pedagogical practices and professional identity formation learning outcomes for students. Conclusions: This scoping review illustrates the range of contexts in which nursing students learn, the multidimensional nature of identity formation, as well as the breadth of pedagogical practices and learning outcomes that guide course design. The results can be used to inform future curriculum planning and to identify focused research questions to extend our understanding of evidence-based teaching practices supporting professional identity formation.